RESEARCHES OF SOCIAL STRATIFICATION AND ITS INFLUENCE ON DYNAMICS OF FORMING OF CIVIL SOCIETY IN UKRAINE - Довбня, О.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article on the basis of analysis of modern sociological literature and publicistic materials the features of contradictory process of social stratification of modern Ukrainian society and influence of these process on the berth of civil society are revealed. Basic directions of changes what is going on in this sphere are shown.